2005
DOI: 10.1210/jc.2004-2054
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Pharmacokinetics and Tolerability of Alendronate 35- and 70-Milligram Tablets in Children and Adolescents with Osteogenesis Imperfecta Type I

Abstract: The mean oral bioavailability of 35- and 70-mg ALN tablets was less than 0.6%, comparable to adult studies. Adverse experiences from single-dose ALN were minor, and the drug was generally well-tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 26 publications
0
33
0
2
Order By: Relevance
“…A pharmacokinetics study of oral, weekly alendronate in children with mild OI recently showed that the absorption was <1%, comparable to adult studies [98], and that there were documented side effects similar to the acute phase reaction observed with intravenous pamidronate. Alpadronate, administered as weekly tablets to children with severe OI, was shown to positively impact on bone mass, density, and fracture rates, although reshaping of compressed vertebrae and mobility were unchanged after 2 years’ treatment in this randomized, controlled trial of 34 patients [99].…”
Section: Approach To Diagnosis and Treatmentmentioning
confidence: 68%
“…A pharmacokinetics study of oral, weekly alendronate in children with mild OI recently showed that the absorption was <1%, comparable to adult studies [98], and that there were documented side effects similar to the acute phase reaction observed with intravenous pamidronate. Alpadronate, administered as weekly tablets to children with severe OI, was shown to positively impact on bone mass, density, and fracture rates, although reshaping of compressed vertebrae and mobility were unchanged after 2 years’ treatment in this randomized, controlled trial of 34 patients [99].…”
Section: Approach To Diagnosis and Treatmentmentioning
confidence: 68%
“…To provide equivalent oral and intravenous doses, it was assumed based on available in vitro and in vivo data that the oral alendronate dose had 0.5% intestinal absorption, (20) 50% skeletal bioavailability, (21) and five times greater potency than intravenous pamidronate. (22) Thus, daily oral alendronate over 4 months was considered to be equivalent to intravenous pamidronate given over 3 consecutive days, every 120 days.…”
Section: Methodsmentioning
confidence: 99%
“…Adverse effects of bisphosphonates are few and minor in this population (gastrointestinal complaints, fever, headache, small decreases in lymphocyte counts). 54,59,60 Flu-like symptoms described as "acute phase reactions" are common with IV administration of bisphosphonates with the first infusion. 54,59 The results presented in the Cochrane review provide evidence, albeit in a relatively small population, of significant improvement in BMD in individuals with OI when treated with either oral or IV bisphosphonates.…”
Section: Bisphosphonate Therapymentioning
confidence: 99%